COMPOSITION OF DIAMONDOIDS IN OIL SAMPLES FROM THE ALPINE FORELAND BASIN, AUSTRIA: POTENTIAL AS INDICES OF SOURCE ROCK FACIES, MATURITY AND BIODEGRADATION. (April 2017) - Pytlak, Ł.; Kowalski, A.; Gross, D.; Sachsenhofer, R.F.
Abstract : Twenty‐seven oil samples from Cretaceous, Eocene and Rupelian reservoir rocks in the Alpine Foreland Basin (Austria) were analysed to evaluate the composition of diamondoid hydrocarbons using gas chromatography – triple quadrupole mass spectrometry. The oils were generated from marly and shaly Oligocene source rocks buried beneath the nappes of the Alpine foldbelt to the south of the study area. Diamondoid hydrocarbons were detected in the saturated fraction of all the analysed oils. A biodegraded oil sample from a shallow reservoir in the NE part of the study area showed an enrichment in diamondoids due to the molecule's high resistance to microbial degradation. Variations in the organic matter type of the source rock facies and differences in maturity are known to influence the composition of diamondoids. However in this study, biomarker‐derived maturity parameters do not show a convincing correlation with diamondoid maturity parameters. Moreover, no cracking trend based on biomarkers and diamondoid concentrations was observed. The results indicate that the composition of diamondoids in oils from the Austrian part of the Alpine Foreland Basin is mainly controlled by heterogeneities in the Lower Oligocene source rocks, including the occurrence of a redeposited source rock succession in the western part of the study area. By contrast, EAI‐1 (the ethyladamantane index) shows a good correlation with various maturity parameters and seems to be independent of source rock facies.